Clinical and epidemiological profile of patients affected by chikungunya admitted to a referral hospital for infectious diseases - Braga , Mayra Madeira; Anfrisio , Millena Oliveira; Peres, Dalila Augusto (Seven Editora, 2023)
Introduction: Chikungunya (CHIK) is an infectious disease caused by the CHIK virus, an alphavirus belonging to the Togaviridae family, transmitted through the infected bite of the Aedes aegypti and Aedes albopictus mosquitoes. Objective: To describe the clinical and epidemiological profile of patients affected by chikungunya admitted to a referral hospital for infectious diseases. Methods: Cross-sectional and descriptive research with a quantitative approach. The population consisted of neonates, children and adults with a laboratory-confirmed diagnosis of chikungunya and who were admitted to a referral hospital from 2015 to 2018. Data were collected from medical records and the SINAN and LACEN Information Systems. The analysis was performed through the frequency distribution. Results: The profile of the 52 patients showed that 30 (57%) lived in Fortaleza, 29 (55.8%) were female, the predominant age group was between 0 and 10 years old, with 27 (51%) , 24 (46.2%) were brown. 27 (51.9%) did not start their school activities because of their age. As for signs and symptoms, the most prevalent was fever 51 (98%). As for comorbidities, 41 (78.85%) had no comorbidities. As for the admission criterion, 18 (36.4%) were neurological involvement. Regarding the outcome, 49 (94%) were discharged from hospital. Conclusion: Of those hospitalized, there was a higher prevalence in female children in the preschool phase, of mixed color and living in urban areas. Regarding the admission criteria, a large number of patients with neurological impairment were evidenced and who progressed to discharge. DOI:https://doi.org/10.56238/innovhealthknow-043